Case studies for the new professor : surviving the jungle of the academy - Cox, Thomas D. (Innovative perspectives of higher education., 2014)
For many academics preparing to enter into the world of teaching and scholarly work in higher education institutions, formal graduate education provides discipline specific content. However, there is a practical side of academic preparation that goes unaddressed. The overall objective of Case Studies for the New Professor: Surviving the Jungle of the Academy is to provide case studies ('what if' scenarios) that augment the discipline specific content of those preparing to become professors.The significance of this volume lies in its usefulness as a 'go to' book that addresses situations, contexts, and examples of issues that new professors or administrators in higher education face. The case studies focus on issues that professors may face with students, colleagues, administrators, and other constituencies with whom they may have contact. This 'case studies' approach is significant also in that each one pays special attention to providing a complete narrative to the extent that it is the eyes and ears for an outside reader to understand what happened in that situation. Each case is followed by reflective and analytical questions for readers to begin shaping their own professional responses and reactions in order to cultivate understanding and decision making skills which will result in positive and productive experiences.